GROWTH AND HISTOLOGY OF CATFISH LIVER (Clarias sp) WITH THE ADMINISTRATION OF KATUK LEAVES SIMPLICIA (Sauropus androgynus) - Awaludin Awaludin; Siti Jumariah; Rukisah (Jurnal Harpodon Borneo, 2025)
Catfish (Clarias sp) production has not been stable from year to year. Increasing catfish production has been developed in various ways: adding ingredients rich in natural nutrients, such as katuk leaves. Katuk leaves (Sauropus androgynus) are herbal plants that contain high fatty acids and can increase the metabolism and growth of catfish (Clarias sp). This study aims to determine the effect of adding katuk leaves powder (S. androgynus) as an alternative ingredient in commercial fish feed mixtures on increasing catfish growth (Clarias sp). This study was conducted for 30 days using a completely randomized design (CRD) with three treatments and three replications, namely P1: (control), P2: (commercial feed and katuk leaves powder 100 grams/kg), P3: (commercial feed and katuk leaves powder 150 grams/kg). Based on the results of the study, it showed that the provision of katuk leaves had a significant effect on growth in length, weight growth, SGR (Specific Growth Rate), and FCR (Feed Conversion Ratio) in catfish. The Number of hepatocyte cells found in histological observations showed that the highest Number of hepatocyte cells were in treatment P3 (225,636), treatment P2 (224,560), and the lowest in P1 (218,756). The best feed to increase growth is P3. Based on the research results on commercial feed mixed with katuk leaves powder (S. androgynus) containing fatty acids, it can increase the growth of catfish (Clarias sp) observed from the growth and morphology of liver cells.